Down‐regulation of the Sp1 transcription factor by an increase of microRNA-4497 in human placenta is associated with early recurrent miscarriage - Huaiyun Tang; Linqing Pan; Yun Xiong; Leilei Wang; Yugui Cui; Jiayin Liu; Lisha Tang (BMC, 2021)
Abstract Background The pathophysiological mechanism of recurrent miscarriage (RM) is unclear. The goals of this study were to determine the role of microRNA-4497 overexpression in placental villus tissues in early RM; To identify the potential target mRNAs of miRNA-4497; And to investigate the microRNA-4497-mediated regulatory mechanisms in placental trophoblasts. Methods Bioinformatics analysis was performed to identify the candidate target genes of miRNA-4497. The protein expression of Sp1 transcription factor (SP1), chemokine (C-X-C motif) receptor 5 (CXCR5) and bone morphogenetic protein 8a (BMP8A) were determined in the villus tissues of the RM and normal groups by Western blotting and immunohistochemistry. Cultured 293T cells were co-transfected with the miRNA-4497 agomir or luciferase reporter vectors containing the wild-type or mutant 3'-UTRs of the target mRNAs to verify the regulatory role of miRNA-4497. Results Bioinformatics analysis suggested that SP1, CXCR5 and BMP8A mRNAs are potential targets of miRNA-4497. The expression of SP1, CXCR5 and BMP8A proteins in the chorionic villus tissues of RM placentas were significantly decreased compared to those in the normal controls. Moreover, SP1 protein levels were inversely correlated with the levels of miRNA-4497 in the placentas of RM patients and normal controls. The expression of SP1 mRNA and protein were down-regulated in HTR-8/SVneo cells after forced overexpression of the miRNA-4497 agomir. The results of the co-transfection assay showed that mutation of the miRNA-4497-binding sites in the 3'-untranslated region (3'-UTR) of SP1 led to a recovery of luciferase activity upon overexpression of miRNA-4497, suggesting that SP1 could be a direct target of miRNA-4497. Conclusions An increased miRNA-4497 level in the placental villus tissues associated with recurrent miscarriage may down-regulate SP1 expression. The negative regulation of SP1 by miRNA-4497 may potentially contribute to the pathogenesis of recurrent miscarriage through promotion of trophoblast apoptosis. These findings provide novel information on the regulation of placental trophoblast apoptosis, and could be useful for the development of new therapeutic strategies for better management of recurrent miscarriage.